A COMPARATIVE ANALYSIS OF ‘WITCHCRAFT PERSECUTIONS’ IN NIGERIA AND TANZANIA USED AS A TOOL TO MARGINALIZE CHILDREN - Murungi, Nkatha (University of Pretoria, 2022)
Mini Dissertation (LLM (Human Rights and Democratization in Africa)--University of Pretoria, 2022.